Analisis Sensori dan Daya Terima Konsumen terhadap Snack Bar Gluten-Free berbasis Tepung Pisang, Sorgum dan Talas - Elfani Devitasari; Dicky Aditya Warman; Nur Rizqi Bariroh; Ahmad Zamroni (Program Studi Teknologi Hasil Pertanian, 2026)
This study aims to analyze the sensory characteristics and consumer acceptance of gluten-free snack bars made from banana flour, sorghum flour, and taro flour, each used as the main ingredient separately. The study used a completely randomized design (CRD) with three treatments: banana flour snack bars (P1), sorghum flour snack bars (P2), and taro flour snack bars (P3), each with three replicates. Sensory evaluation was conducted by 30 semi-trained panelists using hedonic and descriptive intensity tests for the attributes of color, aroma, texture, and taste. The data were analyzed using analysis of variance (ANOVA) at a 5% significance level. The results showed that the type of flour affected the aroma and taste attributes but had no significant effect on the likability scores for color and texture. The banana flour-based snack bars received the highest likability scores for color (3.80) and taste (3.47), while the sorghum flour-based snack bars received the highest likability score for aroma (3.87) and the highest color intensity score (4.60). All treatments showed a relatively similar level of texture acceptability, with a score of 3.07. The taro flour-based snack bars received the lowest scores for aroma and flavor. The results of the study indicate that banana flour and sorghum flour have better sensory characteristics and higher levels of consumer acceptance than taro flour, making them potential raw materials for the development of gluten-free snack bars based on local foods.